Football and discrimination: Antisemitism and beyond - Brunssen, Pavel; Schüler-Springorum, Stefanie (Critical research in football, 2021)
Introduction 1 PAVEL BRUNSSEN AND STEFANIE SCHÜLER-SPRINGORUM PART I Prologue 9 1 Collective identity and forms of abuse and discrimination in football fan culture: A case study on antisemitism 11 EMMA POULTON PART II Ressentiment 35 2 The image of the "Judenklub" in interwar European soccer: Myth or reality? 37 RUDOLF OSWALD 3 The sociopolitical roots of antisemitism among football fandom: The real absence and imagined presence of Jews in Polish football 47 JACEK BURSKI AND WOJCIECH WOŹNIAK 4 Antisemitism in German football since the 1980s 65 FLORIAN SCHUBERT 5 Antisemitic ressentiment-communication directed at RB Leipzig in German football fan culture: The third other 81 PAVEL BRUNSSEN PART III Identity 95 6 Self-directed racialized humor as in-group marker among migrant players in a professional football team: "Dude, Just Draw the Racist Card!" 97 SOLVEJG WOLFERS 7 Racism and interethnic conflict in Amateur football: The case of migrant sports clubs in Germany 111 SILVESTER STAHL 8 Struggling to belong in the face of otherness: The Atlanta Fútbol club of Buenos Aires 127 RAANAN REIN PART IV (Anti-)discrimination 139 9 Appealing to a common identity: The case of antisemitism in Dutch football 141 JORAM VERHOEVEN AND WILLEM WAGENAAR 10 Eintracht Frankfurt fans and the museum: Football history, remembrance culture, and the fight against antisemitism 152 MATTHIAS THOMA AND MARTIN LIEPACH 11 A comment on several specific aspects of remembrance and education projects in football 166 ANDREAS KAHRS 12 The twofold American exceptionalism in soccer fandom: Anti-discriminatory activism among organized soccer supporters in the US 179 MARKUS GERKE PART V Epilogue 197 13 What is it about association football -- the arrogantly self-appointed "Beautiful Game" -- that renders most (though not all) of its fan cultures so ugly? 199 ANDREI S. MARKOVITS